What is colaborative teaching? - Dos Santos, Camila Elidia Messias [UNESP]; da Costa, Lorinisa Knaak [UNESP] (FapUNIFESP (SciELO), 2020)
The work What is Collaborative Teaching? intends to disseminate scientific knowledge in a more accessible language for teachers, allowing them to review their pedagogical practices, with the aim of making them more inclusive. In a dynamic and illustrative way, the study was organized into five chapters. In the first, the authors discuss the introductory foundations referring to Special Education from the perspective of Inclusive Education. In the subsequent chapters, Collaborative Teaching is presented in an illuminating way, alluding to its concept, its characteristics and how it can be implemented. The fourth chapter deals with reflections on the inclusive school, the roles and responsibilities of each professional for the development of the school curriculum. The work is complemented with research experiences on Collaborative Teaching carried out in Brazil. In the final considerations, some questions and reflections about the adoption of Collaborative Teaching are highlighted. Finally, a section with frequent doubts expressed by teachers and school staff is presented, when the school chooses to work in collaboration and starts its implementation.
O que é ensino colaborativo?
Keywords: Inclusive education; Pedagogical practice; Special education